Stones that Made Food. A Lithic Viewpoint on Food Production Practices in the Early Mediterranean Neolithic - Mazzucco, Niccolò (Food & History, 2021)
Abstract Food gathering and production are daily and fundamental activities for the reproduction and development of human societies, now and in the past. Food practices are deeply embedded in social, cultural, environmental and technological settings. During prehistory, for example, the most important changes in lithic technology were linked to the appearance of new techniques for obtaining food: more effective, requiring less time and fewer raw materials or simply better suited to the environmental and cultural framework. With the transition towards a farming economy, new food practices appeared, which gave rise to new skill sets, technologies and knowledge. This article focuses on the flaked stone tools of the Early Mediterranean Neolithic and their use for the obtainment of foodstuffs from both vegetal and animal resources. In particular, this article concerns the stone tools and techniques associated with hunting, animal slaughter and butchering, as well as with crop harvesting tasks. How were those tools made and how were they used? Were those tools crucial for food production? What factors influenced their geographical and chronological variability? What can we learn about early farming societies and their economic organization by studying them? Abstract La collecte et la production de nourriture sont des activités quotidiennes et fondamentales pour la reproduction et le développement des sociétés humaines, aujourd’hui comme dans le passé. Les pratiques alimentaires sont profondément ancrées dans des contextes sociaux, culturels, environnementaux et technologiques. Au cours de la Préhistoire, par exemple, les changements les plus importants dans la technologie lithique ont été liés à l’apparition de nouvelles techniques pour se procurer de la nourriture : plus efficaces, nécessitant moins de temps et moins de matières premières ou simplement mieux adaptées au cadre environnemental et culturel. Avec la transition vers une économie agricole, de nouvelles pratiques alimentaires sont apparues, qui ont donné lieu à de nouvelles compétences, technologies et connaissances. Cet article se concentre sur les outils en pierre taillée du Néolithique ancien méditerranéen et leur utilisation pour l’obtention de denrées alimentaires à partir de ressources végétales et animales. En particulier, cet article concerne les outils en pierre et les techniques associées à la chasse, à l’abattage et au dépeçage des animaux ainsi qu’aux tâches de récolte des cultures. Comment ces outils étaient-ils fabriqués et comment étaient-ils utilisés ? Ces outils étaient-ils essentiels à la production alimentaire ? Quels facteurs ont influencé leur variabilité géographique et chronologique ? Que pouvons-nous apprendre sur les premières sociétés agricoles et leur organisation économique en les étudiant ?